The role of pre-school quality in promoting resilience in the cognitive development of young children - Hall, J; Sylva, K; Melhuish, E; Sammons, P; Siraj-Blatchford, I; Taggart, B (Taylor and Francis (Routledge), 2009)
The study reported here investigates the role of pre-school education as a protective factor in the development of children who are at risk due to environmental and individual factors. This investigation builds upon earlier research by examining different kinds of 'quality' in early education and tests the hypothesis that pre-schools of high quality can moderate the impacts of risks upon cognitive development. Cognitive development was measured in 2857 English pre-schoolers at 36 and 58 months of age, together with 22 individual risks to children's development, and assessments were made of the quality of their pre-school provision. Multilevel Structural Equation Modelling revealed that: the global quality of pre-school can moderate the effects of familial risk (such as poverty); the relationships between staff and children can moderate the effects of child level risk (such as low birth weight); and the specific quality of curricular provision can moderate the effects of both. Policy makers need to take quality into account in their efforts to promote resilience in young 'at risk' children through early childhood services.